Discovery Learning Widely Applied at Junior Level with Positive Learning Outcome: Pembelajaran Penemuan Diterapkan Secara Luas di Tingkat Sekolah Menengah Pertama dengan Hasil Belajar yang Positif - Umami, Thessa Sahara; Agustini, Ketut; Suartama, I Kadek (Indonesian Journal of Innovation Studies, 2025)
General Background: Discovery learning has emerged as a pivotal instructional model aligned with 21st-century educational demands. Specific Background: Despite its recognized potential, comprehensive syntheses of its effectiveness, implementation patterns, and challenges remain limited. Knowledge Gap: Previous studies tend to explore discovery learning in isolated contexts without offering systematic insights across educational levels and recent developments. Aims: This study employs a Systematic Literature Review (SLR) using the PRISMA framework to examine 18 peer-reviewed articles published from 2020 to 2024, aiming to explore (1) the predominant educational level applying discovery learning, (2) its impact on learning outcomes, (3) the model's effectiveness, and (4) challenges in its implementation. Results: The analysis reveals that discovery learning is most widely implemented at the junior secondary (SMP) level. It consistently enhances students’ conceptual understanding, critical thinking, motivation, and academic performance. Novelty: This study uniquely synthesizes multi-year empirical evidence to highlight the adaptability and constraints of discovery learning across modalities, including technology-assisted instruction. Implications: Findings underscore the importance of targeted teacher training and infrastructure development to optimize implementation. This synthesis informs educators and policymakers of strategic directions for embedding discovery learning in modern pedagogical frameworks. Highlights: Highlights SMP as the dominant level using discovery learning. Emphasizes positive effects on critical thinking and motivation. Identifies time, readiness, and facilities as key obstacles Keywords: Discovery Learning, Systematic Literature Review, Learning Outcomes, Educational Challenges